Haemoglobin Phenotype of Newborn at Asaba Specialist Hospital, Delta State Nigeria: The Need for Newborn Screening - Peace, Ighosewe A.; Ajaegbu, Obinna; Angela, Bolum-Okolie N.; Helen, Ogbangwo O.; Lynda, Nwanne C.; Benedeth, Omeni N.; Bertilla, Ezeonwu U.; Ifeoma, Okwudinka O.; Nkemjika, Mbagwu E. (International Journal of Innovative Research in Medical Science, 2024)
Background: Sickle cell disease (SCD) is an inherited autosomal recessive haemoglobin disorder that contribute significantly to the morbidity and mortality of children especially in Nigeria. Despite the high morbidity and mortality associated with SCD in Nigeria, early detection through newborn screening is not readily available. This study is aimed at documenting the different pattern of haemoglobin phenotype among the neonate following institutionalization of newborn screening for SCD. Subjects and methods: A prospective study involving eligible newborn babies seen in Asaba Specialist Hospital between January 2021 and December 2023. Venous blood was collected from the babies into an ethylenediaminetetraacetic acid sample bottles. The samples were analyzed using high‑performance liquid chromatography (HPLC) techniques, and the haemoglobin phenotypes obtained were documented. Data were analyzed using the Statistical Package for Social Sciences (SPSS) version 23. Results: A total of 5,103 neonates were recruited during the period under review. Majority (3297; 79.1%) of the subject had FA (normal Phenotype) while 801 (19.2%), 45 (1.0%), 19 (0.4%), 7 (0.2%), 1 (0.02%) had haemoglobin phenotype FAS, FS, FAD, FAC and FAE respectively. Conclusion: There is presence of wide spectrum of abnormal haemoglobin phenotype among the subjects. We recommend that newborn screening for sickle cell disease should routinely done for all neonate in Nigeria.